Perencanaan Taman Wisata Alam Danau Tamblingan Buleleng, Bali - Plaituka, Randy Daserona; Sugianthara, Anak Agung Gede; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Planning for Tamblingan Lake N atural Park Buleleng , Bali . The T amblingan lake's natural tourist park has a potential of attractions that are aided by both its unique and strategic location. This makes the T amblingan natural park a highly prospecting area that is able to attract tourists and plan the park's natural parks. The study intended to set up a zoning plan for lake tamblingan natural tourist park. The method in this study used survey method. By the stage of planning starting from the preparation stage, inventory, analysis, synthesis, concept, and planning. This research has a site plan. The attractive, environmentally insightful concept of tourism is based on the potential resources of landscapes and attractions and tourist attractions to preserve the landscape's resources and sustainability. The end result of the study was the landscape plans for the natural park areas of T amblingan lakes involving the distribution of space, circulation, activity, and facilities .